2005
DOI: 10.1158/0008-5472.can-05-0288
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for G2 Arrest Induced by 2′-C-Cyano-2′-Deoxy-1-β-d-Arabino-Pentofuranosylcytosine and Consequences of Checkpoint Abrogation

Abstract: Abstract2V -C -cyano-2V -deoxy-1-B-D-arabino -pentofuranosylcytosine (CNDAC) is a nucleoside analogue with a novel mechanism of action that is currently being evaluated in clinical trials. Incorporation of CNDAC triphosphate into DNA and extension during replication leads to single-strand breaks directly caused by B-elimination. These breaks, or the lesions that arise from further processing, cause cells to arrest in G 2 . The purpose of this investigation was to define the molecular basis for G 2 checkpoint a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 49 publications
7
49
1
Order By: Relevance
“…Since these effects of 5FU should trigger the DNA damage and replication checkpoints, respectively, both of which are controlled primarily by the Chk1 protein kinase in vertebrate cells (Bartek et al, 2003), we investigated how genetic inactivation of Chk1 by gene targeting affects the cell cycle response and survival of DT40 B-lymphoma cells exposed to 5FU . Our findings differ in several respects from those of other recent studies which have used pharmacological or siRNA approaches to assess the effect of Chk1 inhibition on tumour cell responses to 5FU (Xiao et al, 2005) and other antimetabolite drugs (Shi et al, 2001;Liu et al, 2005;Morgan et al, 2005). The exact consequences of Chk1 inhibition appear to vary according to the nature of the genotoxic agent examined, however, mitotic division with damage or premature entry to mitosis with incompletely replicated DNA combined in each case with an increased frequency of apoptosis has been documented in a variety of cell types (Shi et al, 2001;Liu et al, 2005;Morgan et al, 2005;Xiao et al, 2005).…”
Section: Discussioncontrasting
confidence: 99%
“…Since these effects of 5FU should trigger the DNA damage and replication checkpoints, respectively, both of which are controlled primarily by the Chk1 protein kinase in vertebrate cells (Bartek et al, 2003), we investigated how genetic inactivation of Chk1 by gene targeting affects the cell cycle response and survival of DT40 B-lymphoma cells exposed to 5FU . Our findings differ in several respects from those of other recent studies which have used pharmacological or siRNA approaches to assess the effect of Chk1 inhibition on tumour cell responses to 5FU (Xiao et al, 2005) and other antimetabolite drugs (Shi et al, 2001;Liu et al, 2005;Morgan et al, 2005). The exact consequences of Chk1 inhibition appear to vary according to the nature of the genotoxic agent examined, however, mitotic division with damage or premature entry to mitosis with incompletely replicated DNA combined in each case with an increased frequency of apoptosis has been documented in a variety of cell types (Shi et al, 2001;Liu et al, 2005;Morgan et al, 2005;Xiao et al, 2005).…”
Section: Discussioncontrasting
confidence: 99%
“…Our data are consistent with the hypothesis that cells treated by sapacitabine or CNDAC may directly progress into G 2 /M phase of cell cycle. Other authors indicated that after incubation with cytostatic concentrations of CNDAC, cell cycle progression was delayed during S phase, but that cells arrested predominantly in the G 2 phase (Azuma et al, 2001;Liu et al, 2005). This unique cell cycle arrest pattern was related to the strandbreaking action of CNDAC caused by the b-elimination-mediated mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…DNA strand breaks that arise from further processing initiate signals that activate the G 2 checkpoint pathway, ultimately resulting in cellular apoptosis. After incubation with cytostatic concentrations of CNDAC, cell cycle arrest in G 2 occurs following a delayed S phase (Liu et al, 2005). This differs from other deoxycytidine analogues such as ara-C or gemcitabine for which the predominant biological alterations consist of cell cycle arrest in S phase (Azuma et al, 2001).…”
Section: Sapacitabine (mentioning
confidence: 94%
See 1 more Smart Citation
“…The DNA nick results from the rearrangement of the CNDAC molecule to form 2 ¶-C -cyano-2 ¶,3 ¶-didehydro-2 ¶,3 ¶-dideoxycytidine (CNddC), which is a de facto DNA chain terminator (16). Unlike the nucleoside analogues 1-h-D-arabinofuranosylcytosine, gemcitabine, and fludarabine that cause S-phase arrest, cells respond to this damage by activating the G 2 checkpoint (17). Although CNDAC-induced cell cycle arrest is instituted through activation of the Chk1-Cdc25C-cyclin-dependent kinase 1 (Cdk1)/cyclin B checkpoint pathway, participants in the signaling events upstream of Chk1 kinase remain obscure.…”
Section: Introductionmentioning
confidence: 99%